Four best practices for strategic planning. Issue 4 (18th July 2016) - Kachaner, Nicolas; King, Kermit; Stewart, Sam
Abstract : Purpose: The authors identify the practices that the companies that get the most benefit from their strategic-planning activities have in common: Design/methodology/approach: The authors describe how successful companies achieve better strategic planning: They explore strategy at distinct time horizons. They constantly reinvent and stimulate the strategic dialogue. They engage the broad organization. They invest in execution and monitoring. Findings: By focusing a standard process on addressing new questions, the strategic dialogue will remain rich, because participants will have new analyses to consider and fundamentally different ideas to discuss; so strategists – and business leaders – have to learn the "art of questioning."" Practical implications: A good approach is to ask the leaders of the business units to identify the most important questions that the center should be asking them in today's turbulent competitive environments." Originality/value: An high-value overview of strategic planning for the novice and seasoned practitioner alike. A well-chosen extended strategy team and an always-on monthly strategy assessment process can be a powerful early-warning system.